STUDI KASUS: IMPLEMENTASI MANUAL KOMPRESI DADA DENGAN MASALAH KEPERAWATAN GANGGUAN SIRKULASI SPONTAN PADA PASIEN HENTI JANTUNG DI IGD - Ardiansyah, Diki; Zahra, Lulu (Yayasan Healing and Healthcare Education, 2024)
Cardiac arrest is one of the biggest causes of death in the world. The success of cardiac arrest treatment depends on the effectiveness, quality, and response time of CPR. Manual chest compressions are considered more effective compared to mechanical chest compressions. Objective to report the result of implementation of manual chest compressions with nursing problem spontaneous circulation disorder in cardiac arrest patients. The writing and data collection method for compiling this scientific paper uses a descriptive case study method which uses interviews, observations, physical examinations, literature studies, and documentation studies presented in the form of narratives, tables, and also pictures. A patient with a hypovolemic shock condition has vomited more than 3 times, coughing with blood, nosebleeds, pulse 134x/minute, breathing frequency 26x/minute that is not treated properly can cause cardiac arrest with an unpalpable carotic pulse, breathing 6x/minute, SPO2 76%, illegible blood pressure, and ECG images show asystole. The main nursing problem is spontaneous circulatory disorders. Manual chest compressions are given for 6 minutes or 3x5 cycles. The evaluation showed the carotid pulse is not palpable, absent of breathing, the patient shows rigor mortis, and ECG images show asystole. Conclusion early recognition and prevention is the most important things to prevent patient from cardiac arrest. The author hopes the implementation of manual chest compressions could solve the nursing problem of spontaneous circulatory disorder in cardiac arrest patients.